Pengukuran Produktivitas Menggunakan Fungsi Cobb-Douglas Berdasarkan Jam Kerja Efektif - Filscha Nurprihatin; Hendy Tannady (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
From time to time the increasing productivity needs to be done to maintain the existence of a company. This research was conducted at a golf glove manufacturing company in Yogyakarta. This study was aimed to compare the productivity of effective working time at production line in 2014 and 2015. This research was using Cobb-Douglas approach. This study shows that the level of productivity in 2015 was higher than in 2014 with the value of the efficiency index in 2014 and 2015 are 54995.07 and 59873.94 respectively. This means that the usage of working hours was increased by 8.87%.Keywords: Productivity, Effective Working Hours, Cobb-Douglas, Efficiency Index